Efficacy, safety and pharmacokinetics of a new high‐purity factor X concentrate in women and girls with hereditary factor X deficiency. (10th April 2018) - Kulkarni, R.; James, A. H.; Norton, M.; Shapiro, A.
Abstract : Essentials Plasma‐derived factor X concentrate (pdFX) is used to treat hereditary factor X deficiency. pdFX pharmacokinetics, safety and efficacy were assessed in factor X‐deficient women/girls. Treatment success rate was 98%; only 6 adverse events in 2 subjects were possibly pdFX related. On‐demand pdFX 25 IU kg −1 was effective and safe in women/girls with factor X deficiency. Summary: Background: A high‐purity, plasma‐derived factor X concentrate (pdFX) has been approved for the treatment of hereditary FX deficiency, an autosomal recessive disorder. Objective: To perform post hoc assessments of pdFX pharmacokinetics, safety and efficacy in women and girls with hereditary FX deficiency. Patients/Methods: Subjects aged ≥ 12 years with moderate/severe FX deficiency (plasma FX activity of < 5 IU dL −1 ) received on‐demand or preventive pdFX (25 IU kg −1 ) for ≤ 2 years. Results: Of 16 enrolled subjects, 10 women and girls (aged 14–58 years [median, 25.5 years]) received 267 pdFX infusions. Mean monthly infusions per subject were higher among women and girls (2.48) than among men and boys (1.62). In women and girls, 132 assessable bleeding episodes (61 heavy menstrual bleeds, 47 joint bleeds, 15 muscle bleeds, and nine other bleeds) were treated with pdFX, with a 98% treatment success rate versus 100% in men and boys. Mean pdFX incremental recovery was similar in the two groups (2.05 IU dL −1 versus 1.91 IU dL −1 per IU kg −1 ), as was the mean half‐life (29.3 h versus 29.5 h). Of 142 adverse events in women and girls, headache was the most common (12 events in six subjects). Six events (two infusion‐site erythema, two fatigue, one back pain, one infusion‐site pain) in two subjects were considered to be possibly pdFX‐related. Following the trial, pdFX was used to successfully maintain hemostasis in two subjects undergoing obstetric delivery. Conclusions: pdFX was well tolerated and effective in women and girls with FX deficiency. Although women and girls had different bleeding symptoms and sites than men and boys, their pdFX pharmacokinetic profile was comparable.